2018
DOI: 10.20944/preprints201810.0274.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does Bilingual Instruction Impact Students' Academic Performance in Content-Based Learning? - Evidence from Business School Students Attending Bilingual and L1 Courses

Abstract: Despite the rapid adoption of bilingual programs (English-Chinese) in China's higher education institutions (HEIs), concerns have been raised on perceived language hindrance to students’ academic comprehension and then performance. In response to this, this paper investigates the effects of bilingual instruction on content-based learning and provides empirical evidence after testing related influential factors in bilingual environment. Analyzing a sample of 498 undergraduate students enrolling in a f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…This finding diverges from the findings from Arco-Tirado et al (2018) and Li (2018), which identified negative effects of medium of instruction on content learning in bilingual courses. However, the finding concurs with the findings from other studies (e.g., Dafouz et al, 2014; Guo et al, 2018; Hernández-Nanclares & Jiménez-Muñoz, 2017); Lin and He (2019), which also found no negative effects of medium of instruction on content learning. There are several explanations for this result.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding diverges from the findings from Arco-Tirado et al (2018) and Li (2018), which identified negative effects of medium of instruction on content learning in bilingual courses. However, the finding concurs with the findings from other studies (e.g., Dafouz et al, 2014; Guo et al, 2018; Hernández-Nanclares & Jiménez-Muñoz, 2017); Lin and He (2019), which also found no negative effects of medium of instruction on content learning. There are several explanations for this result.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, in an investigation of the academic outcomes of a group of English-taught students and a group of Spanish-taught students, Hernández-Nanclares and Jiménez-Muñoz (2017) found that the Spanish-taught and the English-taught students obtained overall similar grades. Similarly, drawing on a sample of 498 undergraduate students enrolled in a core business course at a Chinese university, Lin and He (2019) examined empirically the effects of medium of instruction on content learning between bilingual and L1 classes. Their study also revealed no statistically significant differences in academic performance between the bilingual and the L1 students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concept will feature instructions that fit Language and Communication development which is also an emerging need of ASD education which impact the rise of academic achievements among students in schools, especially learning-disabled students (Nagarkar et al, 2018). The focus on academic performance among students is also from the use of accurate instructions which influence their learning ability, thus increasing achievements in content-based learning (Lin & He, 2019). Thus, it fulfils the demand of the learning for sustainability to further enhance the needs of autism education which also aims to provide the quality education with equality among Malaysian children.…”
Section: Discussionmentioning
confidence: 99%
“…Among those shortcomings, students noted the cursory and superficial nature of explanations provided in class, the periodic lack of linguistic competence in the language of instruction used, a slower-paced course, and the operation of a reduced course (Wilkinson, 2005;Yang, 2015;Arnau, Borras-Comes, & Escobar, 2018). In addition, it is necessary to add that professors also mentioned the lack of linguistic competence on behalf of the students when understanding explanations in class (Sert, 2008;Lo & Lo, 2014;Byun et al 2011;Lin & He, 2019). Nevertheless, studies focused on the academic performance of EMI students are scarce due in part to the inherent difficulties of comparing students' grades from different institutions or the lack of access to those institutions.…”
Section: Bilingual University Degreesmentioning
confidence: 99%